Computer Use and the Employment Status of Older Workers - An Analysis Based on Individual Data - Katrin Schleife (Technische Universität Darmstadt, Department of Law and Economics, 2005)
This paper analyzes computer use by older male employees and estimates the impact of computer use on their employment status, based on individual data from the German Socio-Economic Panel (GSOEP) for the years 1997 and 2001. In line with previous research on the diffusion of new technologies, a strong and negative relationship between the age of workers and computer use is found. In addition, the impact of occupational status and hourly wage on computer use is significantly positive. However, the estimated impact of computer use on the change in employment status of older workers becomes insignificant when controlling for individual and firm-specific characteristics.
Keywords: O33; J26; J14; 330; computer use; older workers; employment status; Computergestütztes Verfahren; Ältere Arbeitskräfte; Erwerbsstatus; Schätzung; Deutschland